ETIKA SEBAGAI LANDASAN BERPIJAK DALAM PENINGKATAN PROFESI TENAGA KEPENDIDIKAN - Hasibuan, Ali Daud (JGK (Jurnal Guru Kita), 2021)
Abstract: Ethics as a Foundation for Professional Improvement of Education Personnel. Educators must also be able to master a lot of knowledge so as not to experience miss communication with their students. In addition, professional educators must also be disciplined in time. Like not arriving late and leaving on time. Also, a teacher should pay attention to his appearance while teaching. An educator must look clean and tidy so that students are also enthusiastic in participating in teaching and learning activities. Keywords: Ethics, Profession, Education Personnel Abstrak: Etika Sebagai Landasan Berpijak Dalam Peningkatan Profesi Tenaga Kependidikan. Pendidik juga harus mampu menguasai banyak ilmu agar tidak mengalami miss comunication terhadap pesera didiknya. Selain itu pendidik yang profesional juga harus disiplin dalam waktu. Seperti tidak datang terlambat dan pulang tepat waktu. Juga seorang guru harus memperhatikan penampilannya saat mengajar. Seorang pendidik harus terlihat bersih dan rapi agar peserta didi juga semangat dalam mengikuti kegiatan belajar mengajar. Kata Kunci: Etika, Profesi, Tenaga Kependidikan